The progression of TRAb-positive subacute thyroiditis and its differential diagnosis from Graves’ disease - Yuan, Saiya; Zhao, Xiaolu; Liu, Fan; Yao, Jinming; Zhao, Junyu (Frontiers in Immunology, 2025)
Subacute thyroiditis (SAT) is a self-limiting thyroiditis with an unclear pathogenesis. Human leukocyte antigen (HLA)-B*35 is considered a predisposing factor, and viral infection is believed to be a trigger. In recent years, elevated levels of thyroid-stimulating hormone receptor antibodies (TRAb) have been observed in some patients with SAT. Typically, these elevated TRAb levels may spontaneously revert to negative as the disease improves. The mechanism of TRAb production may be related to abnormalities in immune surveillance and viral infections. Critically, the presence of TRAb can influence clinical manifestations, complicate diagnosis, and affect recovery in SAT. There are three types of TRAb, yet studies on their changing patterns during SAT remain scarce. Both SAT and Graves’ disease (GD) can cause thyrotoxicosis, leading to difficulties in clinical differential diagnosis, especially when SAT presents with positive TRAb. Currently, studies on TRAb-positive SAT are relatively limited. Therefore, this article reviews the pathogenesis of TRAb-positive SAT and its differential diagnosis from GD, aiming to enhance the understanding of this disease among clinicians.